Endoscopic biodegradable stents as a rescue treatment in the management of post bariatric surgery leaks: a case series - Al Lehibi, Abed; Al Balkhi, Areej; Al Mtawa, Abdullah; Al Otaibi, Nawaf (Endoscopy International Open, 2018)
Background and aims Postoperative leak is one of the most feared complications after bariatric surgery. Endoscopic stenting is used to manage leaks by decreasing the gastrointestinal intraluminal pressure. The main advantage of endoscopic management is providing healing while still allowing for oral nutrition. However, limited literature exists on whether biodegradable stents can be used to control leaks when conventional metallic stents fail.Methods Our series consists of four patients who were found to have a leak as a complication of bariatric surgery. Two patients were initially managed by abdominal/chest drainage, and one required total parenteral nutrition. Conventional endoscopic exclusion techniques with short and long fully covered metallic stents were tried and failed in three of the four patients included in this series. Thus, biodegradable stents were used as a rescue option.Results Biodegradable stents provided immediate improvement for all of the patients, and Gastrografin studies were leak-free 2 days after the procedure. All patients were started on oral feeding and discharged home within 5 – 6 days later. Minimum outpatient follow-up of 8 weeks was achieved with no issues. Follow-up endoscopy was performed 2 – 3 months later in three patients and showed completely resorbed stents. The only drawback was the mucosal reaction to the stent causing dysphagia in two patients, who eventually needed esophageal dilatation.Conclusion Biodegradable stents have the potential to provide a reasonable rescue option to manage post bariatric surgery leaks in patients who fail conventional endoscopic exclusion methods. However, data from larger studies are needed to collect information on which theoretical advantages/disadvantages of degradable biomaterials apply to real practice.